Docking de herbicidas na glutationa transferase tau4-4 de soja (Glycine max) - Mendes, Josiane Enevina (2011)
This study, based on molecular docking, describes the search for the most favorable conformations when complexes between herbicides, used in soybean cultivation, and an enzyme involved in the detoxification process are formed and based on these results some guidelines for the developing of new compounds are proposed. The glutathione transferase Tau, GmGSTU4-4, from soybean was the target protein, and diclofop, fluazifop, Clethodim, clomazone, diquat, paraquat, atrazine, diuron, bentazone, acifluorofem, fomesafem, sulfentrazone, glyphosate and clorimurom, the 14 herbicides studied. These last ones were chosen based on the list of those that are used in soybean crops and are registered with the Ministry of Agriculture and Supply of Brasil. For all of them the GmGSTU4-4-herbicide complexes were obtained. The protein binding site, analyzed by molecular visualization, presents an almost cylindrical shape, open and exposed to the solvent and is composed of two sites G and H. Three water molecules were observed in the G-site in that participate in molecular interactions with several of the studied herbicides, This finding suggests that new compounds that could, and should, be developed need to have in their structure chemical groups capable of interacting with the water, both as donors and acceptors of hydrogen bonds. Another interesting finding was that the largest herbicides may occupy both the G and H sites, and seem to be most promising in the activity of detoxification.